(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Innovation is a watchword in the 21st century and is closely related to creativity. Children can use tools at early ages, but they are poor innovator in tasks that require manufacturing of tools. Here, we discussed a comparative approach to the understanding of innovation from the perspective of human development, as well as an innovation within the behavioral learning framework. Finally, implications of behavioral research to the preschool education are discussed. Keywords: Creativity, Preschool, BNCC, Psychology of Technology